Identification and validation of Fusarium head blight resistance QTL in the U.S. soft red winter wheat cultivar 'Jamestown'. Issue 6 (28th October 2020) - Carpenter, Neal R.; Wright, Emily; Malla, Subas; Singh, Lovepreet; Van Sanford, David; Clark, Anthony; Harrison, Stephen; Murphy, J. Paul; Costa, Jose; Chao, Shiaoman; Brown‐Guedira, Gina L.; McMaster, Nicole; et al.
Abstract: Use of genetic resistance is one of the most important strategies to manage the devastating disease Fusarium head blight (FHB) in wheat. Numerous quantitative trait loci (QTL) having varying effects on reducing FHB and the mycotoxin deoxynivalenol (DON) accumulation have been reported from Asian, European, or distant sources such as wild relatives of wheat ( Triticum aestivum L.). However, coming from nonadapted backgrounds, the incorporation of such QTL into regional breeding programs has often resulted in the simultaneous transfer of other undesirable traits. Therefore, it is important to identify, characterize, and deploy sources of genetic resistance that do not suffer from poor adaptability and/or linkage drag. In the present work, QTL associated with FHB resistance in a high‐yielding, moderately resistant soft red winter wheat cultivar 'Jamestown' were mapped and validated. The QTL mapping was done using a recombinant inbred line (RIL) population of Pioneer '25R47' × Jamestown having 186 individuals. Phenotyping over 2 yr at three locations, and genotyping using the 90K single nucleotide polymorphism (SNP) platform identified two new QTL, named QFHB.vt‐1B.1 and QFHB.vt‐1B.2, on the chromosome 1B long arm. The QTL contributed to FHB incidence, FHB severity, Fusarium‐damaged kernels, and DON content. Independent mapping of these QTL using two additional RIL populations of FG95195 × Jamestown (170 RILs) and Jamestown × LA97113UC‐124 (77 RILs) validated their stability and effectiveness in different genetic backgrounds. Kompetitive allele specific polymerase chain reaction (KASP) assays were developed using linked SNPs for marker‐assisted selection of the QTL. These QTL are being used in breeding programs to develop FHB‐resistant, high‐yielding varieties.